The worldwide spread of ciprofloxacin-resistant Shigella sonnei among HIV-infected men who have sex with men, Taiwan. (April 2016) - Chiou, C.-S.; Izumiya, H.; Kawamura, M.; Liao, Y.-S.; Su, Y.-S.; Wu, H.-H.; Chen, W.-C.; Lo, Y.-C.
Abstract: Ciprofloxacin-resistant shigellosis outbreaks among men who have sex with men (MSM) have not been reported in Asia. During 3 March to 6 May 2015, the Notifiable Disease Surveillance System detected nine non-imported Shigella sonnei infections among human immunodeficiency virus (HIV) -infected Taiwanese MSM. We conducted a molecular epidemiological investigation using a 1 : 5 matched case–control study and laboratory characterizations for the isolates. Of the nine patients, four reported engagement in oral–anal sex before illness onset. Shigellosis was associated with a syphilis report within 12 months (adjusted odds ratio (aOR) 8.6; 95% CI 1.05–70.3) and no HIV outpatient follow-up within 12 months (aOR 22.3; 95% CI 2.5–201). Shigella sonnei isolates from the nine patients were all ciprofloxacin-resistant and the resistance was associated with S83L and D87G mutations in gyrA and S80I mutation in parC . The nine outbreak isolates were discriminated into two closely related pulsed-field gel electrophoresis (PFGE) genotypes and seven 8-locus multilocus variable-number tandem repeat analysis (MLVA8) types that suggest multiple sources of infections for the outbreak and possible under-recognition of infection among Taiwanese MSM. The outbreak isolates were characterized to be variants of the intercontinentally transmitted SS18.1 clone, which falls into the globally prevalent phylogenetic sub-lineage IIIb. Inter-database pattern similarity searching indicated that the two PFGE genotypes had emerged in the USA and Japan. The epidemiological characteristics of this outbreak suggest roles of risky sexual behaviours or networks in S. sonnei transmission. We urge enhanced surveillance and risk-reduction interventions regionally against the interplay of HIV and shigellosis among MSM.